Reconstructing Stenotic Carotid Models from Ultrasound Images - Helena Henriques (2015)
The goal of the presented research is the development of a computational methodology for hemodynamic analysis of carotid bifurcations based on hospital ultrasound images. In this communication, different strategies for segmentation of B-mode ultrasound images towards 3D model reconstruction of the artery bifurcation are discussed. Using a developed semiautomatic segmentation code, lumen contour identification of a patient with carotid disease is presented.